2023
DOI: 10.1186/s12885-023-10883-6
|View full text |Cite
|
Sign up to set email alerts
|

ZDHHC15 promotes glioma malignancy and acts as a novel prognostic biomarker for patients with glioma

Zhen-Yuan Liu,
Tian Lan,
Feng Tang
et al.

Abstract: Background Glioma is the most common and aggressive tumor in the adult brain. Recent studies have indicated that Zinc finger DHHC-type palmitoyltransferases (ZDHHCs) play vital roles in regulating the progression of glioma. ZDHHC15, a member of the ZDHHCs family, participates in various physiological activities in the brain. However, the biological functions and related mechanisms of ZDHHC15 in glioma remain poorly understood. Methods Data from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recent studies have confirmed a clear link between high zDHHC15 expression and the malignant glioma phenotype, and zDHHC15 plays a key role in promoting the proliferation and migration of glioma cells by activating the STAT3 signaling pathway. Researchers have also suggested that zDHHC15 may be a new prognostic biomarker for patients with glioma and that targeting zDHHC15 could provide a promising strategy for the treatment of glioma ( Liu et al, 2023 ). Local anesthetics may attenuate zDHHC15 transcription, reduce GP130 palmitoylation levels and membrane localization, and thus inhibit IL-6/STAT3 signaling activation.…”
Section: The Role Of Zdhhc In Neurological Diseasesmentioning
confidence: 99%
“…Recent studies have confirmed a clear link between high zDHHC15 expression and the malignant glioma phenotype, and zDHHC15 plays a key role in promoting the proliferation and migration of glioma cells by activating the STAT3 signaling pathway. Researchers have also suggested that zDHHC15 may be a new prognostic biomarker for patients with glioma and that targeting zDHHC15 could provide a promising strategy for the treatment of glioma ( Liu et al, 2023 ). Local anesthetics may attenuate zDHHC15 transcription, reduce GP130 palmitoylation levels and membrane localization, and thus inhibit IL-6/STAT3 signaling activation.…”
Section: The Role Of Zdhhc In Neurological Diseasesmentioning
confidence: 99%
“…Recent research has underscored the extensive participation of ZDHHCs in the progression of various diseases. Enhancing glioma malignancy, ZDHHC15 emerged as a potential novel prognostic biomarker for glioma patients [ 25 ]. Palmitoylation played a crucial role in enhancing osteoclast differentiation and activity, presenting itself as a plausible therapeutic target for addressing osteoporosis and other diseases associated with osteoclast dysfunction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an RNAi-based screen targeting, all 23 members of the ZDHHC family in non-small lung cancer (NSCLC) identified ZDHHC5 to be essential for the growth of NSCLC but not normal human bronchial epithelial cells [ 54 ]. In gliomas, inactivation of ZDHHC15 blocked glioma cells proliferation by decreasing activation of Signal Transducer and Activator of Transcription 3 (STAT3) [ 55 ] and knockdown of ZDHHC12 reduced the growth, migration, and invasion capabilities of glioma cells [ 56 , 57 ]. In pancreatic cancer, knockdown of ZDHHC3 impaired tumor progression in a xenograft mice model [ 58 ], whereas inactivation of ZDHHC9 modified the tumor microenvironment from an immunosuppressive to a proinflammatory environment and, thus, suppressed tumor growth [ 59 ].…”
Section: Introductionmentioning
confidence: 99%